Ethical Considerations for Disseminating Research Findings on Gender-Based Violence, Armed Conflict, and Mental Health: A Case Study from Rural Uganda - Jennifer J. Mootz; Lauren Taylor; Milton L. Wainberg; Kaveh Khoshnood (Harvard FXB Center for Health and Human Rights, 2019)
Gender-based violence (GBV) is a major public health problem that is exacerbated in armed conflict settings. While specialized guidelines exist for conducting research with GBV, guidance on disseminating findings from GBV research is scant. This paper describes ethical considerations of designing and disseminating research findings on GBV, armed conflict, and mental health (including alcohol misuse) in conflict-affected settings in Northeastern Uganda. Following completion of two research studies, we conducted a half-day dissemination meeting with local community professionals (n=21) aged 24 to 60. Attendees were divided into small groups and given a quiz-style questionnaire on research findings to prompt discussion. Two primary ethical tensions arose. One ethical consideration was how to disseminate research findings equitably at the participant level after having taken care to collect data using safe and unharmful methods. Another ethical issue concerned how to transparently share findings of widespread problems in a hopeful and contextualized way in order to facilitate community response. We recommend planning for dissemination a priori, engaging with partners at local levels, and grounding dissemination for action in evidence-based practices.